Numerical and Statistical Sensitivity Analysis of Deterministic and Stochastic SVEITR Model for Measles Infection. (European Journal of Pure and Applied Mathematics, 2025)
Measles is a global health concern due to its high contagiousness and rapid transmission, especially in low-vaccination areas. This article uses an SVEITR model to explain measles transmission and control dynamics. The model is stable at two equilibria and can be verified using the Non-Standard Finite Difference (NSFD) technique. The study offers valuable advice to public health professionals and legislators working to prevent and manage measles, highlighting the importance of international cooperation and vaccination in preventing the disease’s return.
Keywords: Statistical Sensitivity Analysis; The basic reproduction number; Global stability; Lyapunov function; Stochastic SVEITR Model.